Study of Real-Time Slope Stability Monitoring System Using Wireless Sensor Network(WSN) - Dave Ta Teh Chang; Yuh-Show Tsai; Kai-Chun Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Traditional monitoring instruments have been found difficult to meet the requirement for real-time monitoring. This study applied Wireless Sensor Network (WSN) to slope stability monitoring, In recent years, the slopes in Taiwan have frequently caused disasters after heavy rains, and traand understand the process of slope instability from the characterization variation of new concepts. In the first stage, the Mems Sensors were selected and calibrated, and the accuracy was selected as 0.1 。and 0.5。. The self-made tilt calibration apparatus was used to calibrate the accuracy of 33 Mems Sensors respectively placed on the side slope. The stability and repeatability were validated multiple times. The field monitoring was carried out at the second stage. National Highway No. 3 3K+100 and TW PHW62 were selected at test locations, and 23 and 10 sensors were placed at these locations respectively. The data were collected in the in-situ industrial computer, and were transmitted via 3G wireless network card to the remote management unit as the basis of monitoring side slope. This study is now at the overall distribution stage, hoping to use the wireless sensor technology to develop an effective, real-time and energy-saving environmental monitoring system and management platform, so as to construct an intelligent WSN early warning and reporting system, which can be applied to the slope disaster prevention engineering. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2230